Mandarin Conversational Practice Courseware (E-Mandarin) / Mohamad Russzaimie Mohd Rozi - Mohd Rozi, Mohamad Russzaimie (2016)
The development of technology is an affection to the educational field. Courseware is one of the approaches that can be used in teaching and learning process to make it more effective and interesting. This paper demonstrates the development proses of multimedia courseware that can be used for teaching and learning Mandarin language. The purpose of development of multimedia prototype courseware “Mandarin Conversational Practice Courseware” is to simplify of helping teachers to teach students who are taking Mandarin language. This courseware will help students to improve their capabilities in speaking Mandarin language. By developing this courseware, it enables teachers and students to learn faster than usual. Out of the models that are available in instructional design, ADDIE is chosen because of it characteristic. ADDIE has five stages, namely Analysis, Design, Development, Implementation and Evaluation. All the processes that are involved will follow ADDIE model to complete the project. Evaluation is done by selecting 30 respondents and 3 experts from various expertise’s. In term of expert evaluation, six criteria were selected to access the flow of the system, ease of use, screen interface, ease of learning, efficiency and user preferences. The result shows that, most of the experts agree that E-Mandarin Courseware is usable and relevant for student as additional teaching material. Questionnaire was distributed to the respondents to collect data that contain six parts which are content construct, interactivity construct, screen design construct, navigation construct, learnability construct, and student preferences construct. Result from the analysis show that respondents have satisfied in term of Screen Design which are the mean is 4.21 with the standard deviation of 0.122. Meanwhile, in Student Preferences also have the same mean 4.21 with the standard deviation of 0.192. E- Mandarin Courseware can be more reliable and efficient in future, if the entire content is being categorized according to the level of Mandarin Language.